The Impact of Minimum Wages on Wages, Wage Spillovers, and Employment in China: Evidence from Longitudinal Individual-Level Data - Tony Fang; Morley Gunderson; Carl Lin (Institute of Labor Economics (IZA), 2020)
We use the substantial variation in both the magnitude and frequency of minimum wage changes that have occurred in China since its new minimum wage regulations in 2004 to estimate their impact on wages, wage spillovers, and employment. We use county-level minimum wage data merged with individual-level longitudinal data from the Urban Household Survey for the period 2004–09, spanning the period after the new minimum wage regulations were put in place. Our results indicate that minimum wage increases raise the wages of otherwise low-wage workers by a little less than half (41%) of the minimum wage increases. Depending upon the specification, these wage effects also lead to a 2 to 4 percentage point reduction in the probability of being employed, with a 2.8 percentage point reduction being our preferred estimate. We also find statistically significant but very small wage spillovers for those whose wages are just above the new minimum wage, but they are effectively zero for those higher up in the wage distribution.
Keywords: J38; J88; 330; minimum wage; China; wages; employment; wage spillovers